Challenges of Sports Branding - Marija Jankovic; Andjela Jaksic-Stojanovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Nowadays, sport has a much more complex and important role than it used to have in the past from many different points of view- it has become not only a way of everyday life which represents a source of positive energy and contributes to healthier life, but also a symbol of the power of the nations themselves and a kind of business industry which has strong implications on different aspects of social development as well. Today's sports organizations realize their business at a highly profitable level and invest huge money in sports marketing and branding. Contemporary sports marketing is oriented towards a proactive relationship with customers of products and services, as well as with other stakeholders in order to achieve their main goal and to make loyal and satisfactory "consumers". Having on mind the fact that brand represents synonym of quality and that it motivates, runs, empowers and create confidence- it is clear why creating a brand identity and image has a great importance for sports organizations, customers, fans, sports clubs, media, as well as for the country itself.